Implementasi Metode Simpleks dalam Penentuan Jumlah Keuntungan pada Jus Buah - Ritonga, Fahri; Mardianti, Heni; Sari, Kiki Aprida; Putri, Putri; Wardah, Wardah (Indo-MathEdu Intellectuals Journal, 2024)
The problem that is often felt by small MSMEs, such as sellers of fresh fruit juice drinks, is the shortage of ingredients which results in a lack of production. This is an obstacle in terms of linear programming models. To maximize production and production yields, there needs to be a method that can be used to increase production yields and reduce the number of raw material constraints on Mauza Jus. This study aims to determine the implementation of the simplkes method in determining the amount of profit in the fruit jur, in order to increase efficiency and optimal results in a system by applying the simplex method in solving optimization problems. By using the simplex method Mauza Jus can increase profits by up to 60%, this happens because Mauza Jus can determine the amount of production per day and does not experience any losses at all. The processing results are done in QM For Windows. In conclusion, Mauza Jus is getting a considerable increase in profits